Heavy weather (Nature (London), 2011)
According to a New York Times analysis, when Hurricane Andrew made landfall in Florida in 1992 and killed 22 people, it received twice the traditional news coverage that Irene did. Most climate scientists responded equivocally, as scientists do: climate is not weather, and although all extreme weather events are now subject to human influence, global warming driven by greenhouse gases cannot be said to 'cause' any specific manifestation of weather in a simple deterministic sense.